The konyak nagas an indian frontier tribe / Christoph Von Fürer-Haimendorf - Von Fürer-Haimendorf, Christoph (Estados Unidos de América: Holt, Rinehart and Winston, 1969)
Material background, appearnce, dress, and ornament, communitary, tools and housebold implements, landtenure and agriculture, daily life in a Konyak Village; the social structure and its units, morungs as social units; phases of life, pregnancy and birth, premarital affairs of Wakching family, divorce, adultery and illeginimacy, economic obligations between affines; religious beliefs and practices, the fate of the soul, head-hunting rites, the cult of the sky God.
Indexes, maps, tables and images
Col. Soc
Keywords: 1. CULTURE 2. SOCIAL ANTHROPOLOGY 3. SOCIAL CONDITIONS 4. SOCIOLOGY